A socio-hydrological approach for incorporating gender into biophysical models and implications for water resources research. (August 2015) - Baker, Tracy J.; Cullen, Beth; Debevec, Liza; Abebe, Yenenesh
Abstract: Men and women interact with water resources and landscapes in different ways, and there are frequent criticisms that little research is undertaken across disciplines to address this issue. Biophysical scientists in particular struggle with how to integrate "gendered" water uses into models that are necessarily based on prevailing laws and equations that describe the movement of water through the hydrological cycle, independent of social constructs. We explore the challenges faced in developing interdisciplinary and transdisciplinary research approaches and then present a simple yet innovative socio-hydrological approach using participatory three-dimensional maps. As a case study, we describe undertaking this process in Ethiopia where two three-dimensional maps (men's and women's) were separately generated to represent the same 20 km 2 landscape. Mapping results indicated important distinctions in how men and women view landscapes with regard to the number and types of ecosystem services identified. For example, only women identified holy water sites along streams, while men identified twice as many sacred trees on the landscape. There was a clear focus and detailed knowledge about soils among participants in both groups. Maps developed as part of this exercise were successfully used as the principal land use input for the Soil and Water Assessment Tool (SWAT) and results indicate that this is a valid strategy that enhances scientific knowledge and understanding of overall landscapes and ultimately adds value to research for development questions. Highlights: Men and women generate two different three-dimensional maps of the same landscape. Reliance on different ecosystem services is notable across gender. Combining scientific and indigenous knowledge is possible and beneficial in biophysical models.